The Influence of Entrepreneurial Competence, Accounting Information Systems, Financial Report Quality, and Digital Financial Literacy on the Performance of SMEs in East Jakarta - Prasojo, Agil (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to test and analyze four variables, namely entrepreneurial competence, accounting information systems, quality of financial reports, and digital financial literacy on the performance of MSMEs. A total of 100 samples were used in this research, using purposive sampling as a data collection technique. This research uses a quantitative approach by collecting data through online questionnaires from several respondents who are MSMEs in the East Jakarta area. The analytical method used is Partial Least Square – Structural Equation Model (PLS-SEM). The research results show that entrepreneurial competence has an effect on the performance of MSMEs, accounting information systems have no effect on the performance of MSMEs, the quality of financial reports has no effect on the performance of MSMEs, and digital financial literacy has no effect on the performance of MSMEs. Future research is expected to be able to choose a larger sampling technique to represent the population so that the results obtained have good accuracy, and further develop research that can be carried out by replacing or adding other variables to improve the performance of MSMEs and can use new or existing research objects. bigger.